MANAJEMEN PENDIDIKAN KARAKTER SEKOLAH BERASRAMA - Mia; Piter Joko Nugroho; Sumarnie (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
The phenomenon of demoralized among students today requires schools to optimize the management of character education, including through the boarding school system. This study aims to describe the management of boarding school character education in terms of planning, organizing, implementing, monitoring and evaluating aspects, as well as supporting factors and obstacles in character education management at SMP Bethel Rehobot Boarding School Palangka Raya. This study used a qualitative approach with case study design. Data collection techniques through observation, interviews and documentation. Through the purposive sampling technique, the research data sources were determined, including: The Principal, School Foundation, Vice principal of Curriculum, and the Dormitory Manager. Data analysis uses interactive data patterns, including: data collection, data reduction, data presentation, and drawing conclusions/verification. Validation of data using source triangulation technique. The results showed that the management of character education with the boarding school system which is carried out based on the basic principles of management, i.e. planning, organizing, implementing, and monitoring and evaluating, are effective in building and developing the character of students.